2023
DOI: 10.3389/fimmu.2023.1109001
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role for interferons in respiratory viral infections and childhood asthma

Abstract: Respiratory syncytial virus (RSV) and Rhinovirus (RV) infections are major triggers of severe lower respiratory illnesses (sLRI) in infants and children and are strongly associated with the subsequent development of asthma. Decades of research has focused on the role of type I interferons in antiviral immunity and ensuing airway diseases, however, recent findings have highlighted several novel aspects of the interferon response that merit further investigation. In this perspective, we discuss emerging roles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Our data also revealed that infants under 3 years old were more susceptible to respiratory viral infections than children 3–7 years old, mainly due to physiological differences in the respiratory tract and immaturity of the immune system [ 23 , 24 ]. And infants under 3 years old performed worse on NPIs measures than older children, so the study data presented that infants were less sensitive to the protective effect of NPIs measures.…”
Section: Discussionmentioning
confidence: 87%
“…Our data also revealed that infants under 3 years old were more susceptible to respiratory viral infections than children 3–7 years old, mainly due to physiological differences in the respiratory tract and immaturity of the immune system [ 23 , 24 ]. And infants under 3 years old performed worse on NPIs measures than older children, so the study data presented that infants were less sensitive to the protective effect of NPIs measures.…”
Section: Discussionmentioning
confidence: 87%
“… 10 It is also recognized that neutrophil responses to viral infection, like in patients with asthma, are equally heterogeneous and may reflect differing endotypes of wheezing. 11 For example, recent multiomics studies of nasopharyngeal samples (that are predominantly composed of neutrophils 12 ) from young children hospitalized with bronchiolitis have identified discrete endotypes of childhood asthma susceptibility that vary according to viral etiology, underlying type 2–mediated inflammation, and the nature and intensity of the immune response. 13 , 14 To date, neutrophils have been underappreciated in young children with wheezing illnesses10 and there are very limited studies of neutrophil responses to viruses in preschool children with recurrent wheezing.…”
mentioning
confidence: 99%